A Case Series of Patients With Complex Airway Disease and Large Thyroid Tumors Anterior to the Trachea Precluding Tracheostomy - Saira Imran, MBBS; Leon L. Chen, DNP, AGACNP-BC, FCCP, FAANP, FCCM; Michelle Rausen, MS, RRT, RRT-NPS; Luc G.T. Morris, MD, MSc, FACS; Snehal Patel, MD, FRCS; Neil A. Halpern, MD, MCCM, FCCP, FACP (Critical Care Explorations, 2024)
BACKGROUND:. This case series explores the management of respiratory failure in patients with large anterior tracheal thyroid tumors where tracheostomy is not an option. To our knowledge, this study is the first to address the challenges associated with caring for such patients. CASE SUMMARY:. We present the clinical courses of four intubated adults with advanced thyroid cancer and complex airway issues that preclude surgical tracheostomy. Interventions included custom airway stents, long-term intubation, and oncological therapies. Ethical quandaries around patient autonomy and capacity emerged, exacerbated by the absence of viable exit strategies for prolonged intubation, notably the performance of a tracheostomy, causing emotional distress in patients, families, and staff. CONCLUSIONS:. This study showcases the multifaceted challenges in medical, ethical, and emotional domains associated with managing intubated patients with complex disease precluding tracheotomies. We advocate for a nuanced, multidisciplinary, and personalized approach to confront unique issues in airway management, ethical considerations, and disposition.